EESRA: Energy Efficient Scalable Routing Algorithm for Wireless Sensor Networks - Ahmed Elsmany, Eyman Fathelrhman; Omar, Mohd Adib; Wan, Tat-Chee; Altahir, Altahir Abdalla (IEEE access, 2019)
Many recent wireless sensor network (WSN) routing protocols are enhancements to address specific issues with the "low-energy adaptive clustering hierarchy" (LEACH) protocol. Since the performance of LEACH deteriorates sharply with increasing network size, the challenge for new WSN protocols is to extend the network lifespan while maintaining high scalability. This paper introduces an energy-efficient clustering and hierarchical routing algorithm named energy-efficient scalable routing algorithm (EESRA). The goal of the proposed algorithm is to extend the network lifespan despite an increase in network size. The algorithm adopts a three-layer hierarchy to minimize the cluster heads' load and randomize the selection of cluster heads. Moreover, EESRA uses multi-hop transmissions for intra-cluster communications to implement a hybrid WSN MAC protocol. This paper compares EESRA against other WSN routing protocols in terms of network performance with respect to changes in the network size. The simulation results show that EESRA outperforms the benchmarked protocols in terms of load balancing and energy efficiency on large-scale WSNs.